Reconditioning and Testing of the 1984 Toyota Rino Diesel Engine - Hamid Nasrullah; Bahtiar Wilantara; Sulitia Aji Tri Budi Utomo (Politeknik Piksi Ganesha Indonesia, 2022)
The purpose of this research is to get a clear picture of the process of reconditioning and testing the 1984 Toyota Rino diesel engine. And to find out which components must be renovated for excellent engine performance. This research was conducted at the Piksi Ganesha Polytechnic Laboratory of Indonesia. The research method used is qualitative. The result of the reconditioning process is that several diesel engine components must be replaced in gaskets, air, and fuel filters. The results of testing the diesel engine Toyota Rino 1984 are: 1) Injector test, all injectors’ functions should run when tested using a pressure nozzle test; namely, the manometer shows 3000 psi when the lever is pressed, the nozzle can spray fuel tightly, and the nozzle does not leak; 2) Compression test, all cylinders are still in good condition when tested using a cylinder pressure tester, namely the manometer shows the number 30 kg/cm2.